A Distinct Perception on Wire Electrochemical Micromachining of Pure Tungsten with Neutral Aqueous Solution. Issue 13 (1st January 2019) - Gao, Chuanping; Qu, Ningsong
Abstract : Pure tungsten is widely-used in industrial and electrochemical machining (ECM) is favored to machine tungsten. Alkaline solution is preferred in ECM of tungsten. However, alkaline solution isn't environment-friendly, creating the need of greener electrolytes. Neutral solution can dissolve tungsten theoretically since OHˉ can be generated in ECM, which plays the same role as alkaline solution. With neutral solution, bipolar current was used to produce numerous OHˉ for the ECM of tungsten. However, tool cathode wears out when bipolar current is used, indicating its unfeasibility in wire electrochemical micromachining (WEMM, a variation of ECM). An alternative conception is needed for WEMM of tungsten. Actually, the amount of removed material is very tiny in unit time in WEMM. It' possible that OHˉ generated is adequate in WEMM of tungsten with neutral solution, which's worth investigating. Herein, with neutral solution only, WEMM of tungsten is investigated. Electrochemical characteristic of tungsten in different neutral solutions is measured. Experiments are conducted on a series of tungsten foils with such solutions. The experimental results demonstrated that with neutral solution only, a range of tungsten foils (0 to 200 μm) can be well machined by WEMM. Finally, microstructures with excellent morphology are achieved using 0.1 m/l NaNO3 solution.